O perfil espiritual e pastoral do presbítero hoje - Lorscheider, Aloísio (Revista Eclesiástica Brasileira, 2002)
À imagem “tradicional” do Padre, o Autor contrapõe a imagem decorrente da eclesiologia do Vaticano II e das Conferências Gerais do Episcopado Latino-americano de Medellín, Puebla e Santo Domingo. Conclui que os tempos atuais exigem um presbítero engajado social e politicamente, deixando a fé cristã iluminar e animar a vida. Saber qual o perfil mais autêntico do presbítero, hoje, é importante para a pastoral vocacional, o planejamento pastoral, a inserção real no presbitério e o trabalho evangelizador num mundo religioso e culturalmente pluralista. Abstract: To the “traditional” image of the priest, the Author counters with the current picture of the ecclesiology of Vatican II and of the General Conferences of the Latin American Episcopacy of Medellín, Puebla and Santo Domingo. He concludes that the present times demand an involved presbyter in the social and political spheres, permitting the Christian faith room to enlighten and enliven life. To know the most authentic profile of the presbyter today is important for pastoral vocation, pastoral planning, for true integration into the presbytery and the evangelizing work in a religiously and culturally pluralistic world.